Molecular Identification and Phylogenetic-tree Analysis of Hard Ticks from Long Eared Hedgehog Hemiechinus auritus (Gmelin, 1770) in Iraq (Iraqi Journal of Science, 2023)
A total of 77 (35 female and 42 male) hard ticks samples were isolated from 22 long-eared hedgehog during January 2021 to May 2022. All animals were infested with one or two species of hard ticks with 100% infestation rate With the density of infestation mean of 3.5. The areas of collection were Baghdad, Wasit, Karbala and Al-Anbar provinces. Morphological study revealed that both species belonged to one genus of hard ticks: Rhipicephalus sanguineus (Neumann, 1904) 50.64% and Rhipicephalus turanicus (Morel, 1969) 49.35%. The molecular investigation of current study revealed that the sensitive and specific PCR assay allowing rapid and reliable identification of Rhipicephalus sp. by the fragment size amplified, was 390- 400 bp 12S ribosomal RNA gene in Rhipicephalus turanicus and Rhipicephalus sanguineus isolate samples from the under-study animals. The accession numbers in NCBI-Genbank are ON211060 and ON211307 respectively.      Phylogenetic tree analysis was based on small subunit ribosomal RNA gene partial sequence in local Rhipicephalus turanicus Iraqi isolate that was used for genetic relationship analysis. The local Rhipicephalus turanicus Iraqi isolate showed close relationship to NCBI-BLAST Rhipicephalus turanicus from Iran, Turkmenistan, Italy, Greece, Saudi Arabia and the Chinese isolates with total genetic changes at 0.01%. Whereas Phylogenetic tree analysis based on small subunit ribosomal RNA gene partial sequence in local Rhipicephalus sanguineus Iraqi isolate showed clear genetic difference to NCBI-BLAST Rhipicephalus sanguineus isolates from Argentina, Italy, Brazil, France, Portugal, USA and Spain at total genetic changes of 0.005-0.0020%.